# Problem Solving with Algebra MCQs Quiz Worksheet PDF Download

Learn problem solving with algebra MCQs, math online test for elementary school exam prep for distance learning degree, free online courses. Practice algebraic equations and simple inequalities multiple choice questions (MCQs), problem solving with algebra quiz questions and answers for 6th grade assessment test.

Study elementary school courses, online math degree programs MCQs: if four times of certain number 'a' is ten more than thrice number then equation derived for this statement can be written as, for online courses with choices 3a = 4a + 10, 3a = 4a - 10, 4a = 3a - 10, and 4a = 3a + 10 with online eLearning distance education for online degrees course and examination preparation. Free math student portal for online learning problem solving with algebra quiz questions, MCQs to find questions answers based online learning tests.

## MCQs on Problem Solving with Algebra Quiz PDF Download

MCQ: If four times of certain number 'a' is ten more than thrice number then equation derived for this statement can be written as

- 3a = 4a + 10
- 3a = 4a - 10
- 4a = 3a - 10
- 4a = 3a + 10

D

MCQ: Four handbags and three school bags costs $2000 and cost of handbag is thrice as much as schoolbags. If cost of school bag is 'a' then derived equation will be

- 3(4a) - 3a = 2000
- 3(4a) + 3a = 2000
- 3(4a) + 3(3a) = 2000
- 3(4a) - 3(3a) = 2000

B

MCQ: If 'a' denotes unknown value and is increased by 2, result will be 12 then equation for this statement will be

- a + 2 = 12
- 2a = 12
- a = 12 + 2
- a - 2 = 12

A

MCQ: If sum of 4 consecutive numbers is 98 then equation derived for this statement can be written as

- a + (a + 1) + (a + 2) + (a + 3) = 98
- a + 1 + 2 + 3 = 98
- a + (a + 1) + (a + 2) + (a + 3) = 98a
- (a)(1)(2)(3) = 98

A

MCQ: If total sum of money to be divided in three siblings Ana, Ben and Mary is $6000, Ana receives two times as much as Ben receives and Mary receives three times as much as Ben. If Ben receives '$y' then derived equation will be

- 2y + y + 3y = 6000
- 2y - y - 3y = 6000
- 2 + 3 + 1 = 6000y
- 2 - 3 - 1 = 6000y

A